STEAM ENGINE BY USING FRESNEL LENSES - Prof. Sachchidanand J Nimankar, Laxman Yevale, Dhiresh Shivalkar, Rajesh Gupta, Swapnil Bhalekar (International Journal of Research Science and Management, 2017)
This project describes a miniature Steam engine made with the boiler and the Fresnel lens from an old starch copper tube solar water heater. It uses boiler as vaporizer to vaporize the water it receives hot water from the solar heater. Then the steam is injected on the mini engine making it twirl.. A wooden case with a copper tubes encloses all the referred devices. Today, most of the electricity produced throughout the world is from Steam turbines However, electricity is being produced by some other power generation sources such as hydropower, gas power, bio-gas power, solar cells, etc. This project deals with steam cycles used in power plants. Thermodynamic analysis of the Rankine cycle has been under taken to enhance the efficiency and reliability of Steam engines. The thermodynamic deviations resulting in non-ideal or irreversible functioning of various Steam engine components have been identified. Steam engines are located at the water and coal available places. Steam is utilized to run the turbines, by using this Fresnel lenses we are increasing the efficiency of boiler. as well the steam engine.